2021
DOI: 10.1155/2021/5518927
|View full text |Cite
|
Sign up to set email alerts
|

UAV Task Allocation Based on Clone Selection Algorithm

Abstract: With the continuous development of computer and network technology, the large-scale and clustered operations of drones have gradually become a reality. How to realize the reasonable allocation of UAV cluster combat tasks and realize the intelligent optimization control of UAV cluster is one of the most challenging difficulties in UAV cluster combat. Solving the task allocation problem and finding the optimal solution have been proven to be an NP-hard problem. This paper proposes a CSA-based approach to simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The MCMUAVCTAP has garnered significant attention from researchers worldwide, resulting in numerous notable advancements. Reference [8] introduced a Clone Selection Algorithm (CSA) designed to optimize four objectives in multi-UAV task allocation: maximizing the number of successfully allocated tasks, maximizing the benefits of executing tasks, minimizing resource costs, and minimizing time costs. Experimental results demonstrated that CSA outperforms the genetic algorithm in multi-objective UAV task allocation.…”
Section: Related Workmentioning
confidence: 99%
“…The MCMUAVCTAP has garnered significant attention from researchers worldwide, resulting in numerous notable advancements. Reference [8] introduced a Clone Selection Algorithm (CSA) designed to optimize four objectives in multi-UAV task allocation: maximizing the number of successfully allocated tasks, maximizing the benefits of executing tasks, minimizing resource costs, and minimizing time costs. Experimental results demonstrated that CSA outperforms the genetic algorithm in multi-objective UAV task allocation.…”
Section: Related Workmentioning
confidence: 99%
“…UAV task planning is a problem that finds the optimal path with the minimum cost to complete tasks. These path planning problems are usually solved based on one or several optimization criteria, such as time optimization [3,6,15,18], energy optimization [14,20], time and energy mix optimization [13,22,[25][26][27], and hybrid optimization based on coverage [28]. In terms of time optimization, in Reference [3], a time first immune clonal selection algorithm with optimization modification was proposed to solve the task assignment problem of road patrol.…”
Section: Related Workmentioning
confidence: 99%
“…Then, an improved fruit fly optimization algorithm (ORPFOA) was proposed to solve the path planning problem in the initial task sequence and the new task sequence after task change. In [26], for the solution of task assignment problem, four objectives are simultaneously optimized, namely, maximizing the number of tasks successfully assigned, maximizing task execution benefit, minimizing resource cost and minimizing time cost. A multi-UAV task assignment method based on clone selection algorithm is proposed.…”
Section: Related Workmentioning
confidence: 99%
“…The idea of solving it is to construct an assignment model and then calculate the model. To address this problem, a large number of articles has been published, such as mixed integer linear programming [6], simulated annealing [7], particle swarm optimization (PSO) [8], Genetic algorithm [9], and expect system method, etc. Reference [10], starting from the model, uses the expert system method to tackle it.…”
Section: Introductionmentioning
confidence: 99%